Deferasirox for the treatment of iron overload associated with regular blood transfusions (transfusional haemosiderosis) in patients suffering with chronic anaemia: a systematic review and economic evaluation - C McLeod; N Fleeman; J Kirkham; A Bagust; A Boland; P Chu; R Dickson; Y Dundar; J Greenhalgh; B Modell; A Olujohungbe; P Telfer; et al. (Health Technology Assessment, 2009)
Objectives: To assess the clinical effectiveness and cost-effectiveness of deferasirox for the treatment of iron overload associated with regular blood transfusions in patients with chronic anaemia such as beta-thalassaemia major (beta-TM) and sickle cell disease (SCD). Data sources: Electronic databases were searched up to March 2007. Review methods: Methods followed accepted procedures for conducting and reporting systematic reviews and economic evaluations. Results: A total of 14 randomised controlled trials (RCTs) involving a study population of 1480 (ranging from 13 to 586) met the inclusion criteria. There was a high degree of heterogeneity between trials in terms of trial design and outcome reporting. As such it was only possible to meta-analyse serum ferritin data from six trials making comparisons between deferiprone and DFO and combination therapy and DFO. Only one of the results was statistically significant, favouring combination therapy over DFO alone for serum ferritin at 12 months. How this translates into iron loading in organs such as the heart is unclear, nor was it possible to determine the long-term benefits of chelation therapy. Eight full economic evaluations (one full paper; seven abstracts) were included in the review. The results were generally consistent and appear to demonstrate the cost-effectiveness of deferasirox compared with DFO for the treatment of iron overload in a number of different patient populations and study locations. However, a number of assumptions and, in the case of the long-term studies, extrapolation from short-term RCT data were required, which render the results highly speculative at best. Because of the paucity of long-term data we developed a simple, short-term (1 year) model to assess the costs and benefits of deferasirox, deferiprone and DFO in patients with beta-TM and SCD from an NHS perspective. A number of assumptions were required to generate results and, as such, they should be interpreted as indicative rather than factual. Our model suggests that deferasirox may be a cost-effective strategy compared with DFO, at a cost per quality-adjusted life-year (QALY) below £30,000 per year, for patients with beta-TM and SCD. However, this is highly dependent upon the age of the patient and the use and benefits of balloon infusers to administer DFO. Deferasirox compared with deferiprone is likely to be cost-effective only for young children. Furthermore, if deferiprone is proven to offer the same health benefits as deferasirox, the latter will not be cost-effective for any patient compared with deferiprone. Conclusions: In the short term there is little clinical difference between any of the three chelators in terms of removing iron from the blood and liver. Deferasirox may be cost-effective compared with DFO in patients with beta-TM and SCD, but it is unlikely to be cost-effective compared with deferiprone. Elucidating the long-term benefits of chelation therapy, including issues of adverse events and adherence, should be the primary focus for future research. Future work should aim for consistency and transparency in reporting study design and results to aid decision-making when making comparisons across trials.